Integrasi Sistem Peradilan Pemilihan Umum melalui Pembentukan Mahkamah Pemilihan Umum - Moch. Marsa Taufiqurrohman; Jayus Jayus; A'an Efendi (Jurnal Konstitusi, 2021)
Elections that do not end only in counting votes, and instead have to be resolved in the judiciary, have unwittingly become a measure that can legitimize and assess the quality of democracy. This situation confirms that the existence of a judicial institution has become an important part of the sustainability of the election process. This research tries to re-evaluate the implementation process of the Election justice system in Indonesia. By using doctrinal normative legal research collaborated with the Reform Oriented Research method, this study found the problems faced in the Electoral justice system in Indonesia. These problems include the tug of war over regional head election dispute resolution, disintegration and overlapping authority for resolving general election disputes, the accumulation of Election disputes in the Constitutional Court, as well as problems regarding recall system for DPR members by political parties. In resolving these problems, this study offers an idea in the form of integrating the entire Election dispute resolution process in a Supreme Election Court. The Supreme Election Court will be positioned parallel to the Constitutional Court and Supreme Court. The Supreme Election Court has the authority to judge at the first and last levels whose decisions are final and binding to decide on violations of the code of ethics of Election administrators, violations of Election administration, election process disputes, election crimes, over results disputes and post-election disputes